Long-term care and pay-for-performance programs - Edward C. Norton (Asian Development Bank Institute (ADBI), 2017)
The Center for Medicare and Medicaid Services has introduced several pay-for-performance programs in the last few years to encourage hospitals to improve quality of care and reduce costs. Some state Medicaid programs have also introduced pay-for-performance for nursing homes. Long-term care providers play an important role in hospital pay-for-performance programs because they can affect the readmission rate and also total episode payments. A good pay-for-performance program will focus on improving quality of care that affects health outcomes. In addition, that quality must vary across providers and be measurable. Furthermore, it is important that the measures be reported in a timely way, that both demand and supply respond to the measures, and that the measures be risk adjusted. Empirical data from Medicare beneficiaries in the state of Michigan show that mean episode payments and readmission rates in skilled nursing facilities vary widely and are sensitive to the number of observations. These practical matters create challenges for implementing pay-for-performance in practice. There is an extensive literature review of pay-for-performance in long-term care in the United States and in Asia.
Keywords: I11; I13; I18; 330; Economics; China; People's Republic of; Japan; Korea; Republic of Singapore